Participação do óxido nítrico encefálico no controle cardiovascular de rã-touro, Lithobathes catesbeianus - Zena, Lucas Aparecido (Universidade Federal de São Carlos, 2012)
The goal of the present study was to determine if nitric oxide (NO) acting on brain of frogs presents an inhibitory tonus on mean arterial blood pressure (MAP) and heart rate (HR) by reducing the sympathetic activity dependent on α and/or β adrenergic receptors during winter and spring/summer seasons. Thus, body temperature and MAP was measured by a telemetry device implanted into the abdominal cavity of American bullfrogs, with the catheter of the device inserted into the left aortic arch for AP and HR measurements. Additionally, blood cell flux was measured using a laser Doppler flowmeter sutured to the pelvic skin to calculate cutaneous vascular condutance (CVC). A guide cannula was implanted into brain lateral ventricle for injections of L-NMMA (non selective NO synthase inhibitor) or mCSF (mock cerebrospinal fluid, vehycle) and a PE cannula was inserted in the femoral vein for bolus injections of adrenergic antagonists, prazosin (α1) and sotalol (β), and agonists, phenylephrine (α1) and isoproterenol (β) or Ringer solution. Animals were maintained at 25 °C during all the experiments. Mean AP, but not HR, was greater during winter than spring/summer. L-NMMA increased MAP, but did not change HR, during both seasons. The pre-treatment with prazosin attenuated and soltalol accentuated the hypertensive effect of LNMMA in both seasons. We conclude that NO seems to act on the brain of frogs as a hypotensive agent via, at least in part, the inhibition of the symphathetic activity dependent on α, and β, adrenergic receptors.
Keywords: Anfíbio; Óxido nítrico; Sistema cardiovascular; Pressão arterial; Frequência cardíaca; Condutância vascular cutânea; Frequências cardíaca; Sazonalidade; Amphibians; Lithobates catesbeianus; Seasonality; Nitric oxide; Cardiovascular system; Blood pressure, Heart rate; Cutaneous vascular conductance; CIENCIAS BIOLOGICAS::FISIOLOGIA